A study of the breeding structure and some aspects of the parent offspring-relationship in the Elsenburg German Merino stud - Conroy, A. M (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1961.